2012
DOI: 10.3109/09638288.2012.726692
|View full text |Cite
|
Sign up to set email alerts
|

Depression and pain among inpatients with spinal cord injury and spinal cord disease: differences in symptoms and neurological function

Abstract: In general, depressive symptoms were not associated with pain severity in this sample. Etiology was associated with pain, those with traumatic SCI reporting more pain at admission. Among demographic characteristics, age was related to pain, with younger subjects reporting higher levels. These findings suggest that certain characteristics may predispose patients to pain and depression upon admission to rehabilitation. By determining who is at risk for these symptoms, clinicians can adopt treatments that prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Our results were consistent with other studies that showed depressive symptoms and BDI scores were not associated with pain severity [32][33][34]. Tate et al reported that age was related to pain, with younger subjects reporting higher levels [33]. However, Research Hung-Chen Wang Research Hung-Chen Wang when SCI patients with chronic pain had higher depression ratings and their BDI scores were correlated with some of the SF-36 domains (general health, vitality, social functioning and mental health) [35].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results were consistent with other studies that showed depressive symptoms and BDI scores were not associated with pain severity [32][33][34]. Tate et al reported that age was related to pain, with younger subjects reporting higher levels [33]. However, Research Hung-Chen Wang Research Hung-Chen Wang when SCI patients with chronic pain had higher depression ratings and their BDI scores were correlated with some of the SF-36 domains (general health, vitality, social functioning and mental health) [35].…”
Section: Discussionsupporting
confidence: 93%
“…Our results were consistent with other studies that showed depressive symptoms and BDI scores were not associated with pain severity [32][33][34]. Tate et al reported that age was related to pain, with younger subjects reporting higher levels [33].…”
Section: Discussionsupporting
confidence: 93%
“…For example, they include only pain intensity 16,23,25,28,30 ; classify subjects by either pain plus depression 23 or pain versus no pain 8,28,30 ; use pain intensity and interference as predictor and outcome, respectively 1 ; collapse pain interference domains into a single score 1 ; or use only univariate tests (eg, correlations). 7,8,25,30 In addition, the vast majority focus on the chronic period of injury. To fill a gap in knowledge, we examined the independent contributions of pain intensity and pain interference to depression, while accounting for injury and demographic characteristics, antidepressant treatment, and pre-injury binge drinking in a sample of persons with acute SCI.…”
Section: Predictors and Covariatesmentioning
confidence: 99%
“…23 Greater pain has been associated with higher levels of depression in persons with SCI, 16,24 although this is not a consistent finding. 25 Similarly, depression in persons with SCI who also have pain appears to be worse than for persons with non-SCI pain, suggesting that the link between pain and depression may be more intense in the context of SCI. 26 In one of the few studies of pain intensity and depression in an acute SCI rehabilitation setting, Cairns et al 27 found a co-occurrence of pain and depression in inpatient rehabilitation.…”
mentioning
confidence: 99%
“…This resulted in a final sample of 16 independent studies. 11,18,24,26,[29][30][31][32][33][34][35][36][37][38][39][40] Data extraction and organisation…”
Section: Psychosocial Aspects Of Sci Pain J Tran Et Almentioning
confidence: 99%